2017
DOI: 10.1371/journal.pone.0189277
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relatedness of previously Plant-Variety-Protected commercial maize inbreds

Abstract: The emergence of high-throughput, high-density genotyping methods combined with increasingly powerful computing systems has created opportunities to further discover and exploit the genes controlling agronomic performance in elite maize breeding populations. Understanding the genetic basis of population structure in an elite set of materials is an essential step in this genetic discovery process. This paper presents a genotype-based population analysis of all maize inbreds whose Plant Variety Protection certif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
54
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(69 citation statements)
references
References 62 publications
14
54
1
Order By: Relevance
“…Distribution across heterotic groups (HGs) shows 48 inbreds in the Iodent HG, 139 in the non‐stiff stalk HG, and 99 in the stiff stalk HG. Further information about the inbreds used in this study is found in Supplemental Tables S1 and S2, and in Beckett et al (2017). All 285 inbreds were test crossed to PHP02, an ex‐PVP inbred developed by Pioneer Hi‐Bred and located in the Iodent HG.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Distribution across heterotic groups (HGs) shows 48 inbreds in the Iodent HG, 139 in the non‐stiff stalk HG, and 99 in the stiff stalk HG. Further information about the inbreds used in this study is found in Supplemental Tables S1 and S2, and in Beckett et al (2017). All 285 inbreds were test crossed to PHP02, an ex‐PVP inbred developed by Pioneer Hi‐Bred and located in the Iodent HG.…”
Section: Methodsmentioning
confidence: 99%
“…The genotypic dataset is identical to that used in Beckett et al (2017). Briefly, the data came from two different genotype‐by‐sequencing (GBS) runs, with single nucleotide polymorphism (SNP) calls aligned to the B73v2 reference genome.…”
Section: Methodsmentioning
confidence: 99%
“…Nelson et al (2008) found that 92 ex-PVP inbreds separated into six primary genetic clusters founded by inbreds B73, B37, A632 (derived from B14), Oh43, PH207, and Mo17. Recent studies with larger sets of ex-PVP inbreds and single nucleotide polymorphisms (SNPs) continue to support the primary heterotic pools forming subpopulations represented best by the B14, B37, B73, Oh43, Iodent, Iodent Mixed, Lancaster, and Mixed populations (Beckett et al, 2017).…”
Section: Crop Sciencementioning
confidence: 99%
“…This set of materials represents commercialized elite proprietary germplasm protected prior to 1997. In addition, eight public inbreds (B14, B37, B73, B84, H99, Mo17, Oh07, and Oh43) were included for reference based on previous studies of key public founder inbreds (Beckett et al, 2017;Melchinger & Gumber, 1998;Mikel & Dudley, 2006;Nelson et al, 2008;Troyer, 1999).…”
Section: Germplasmmentioning
confidence: 99%
See 1 more Smart Citation